Access to Primary Dental Care and the Work Process of Oral Health Teams: An Analysis of the 3rd Phase of the PMAQ-AB Program - Moângela Alves de Sousa Alencar; Ane Polline Lacerda Protasio; Ana Flávia Uzêda dos Santos Macambira; Ana Maria Gondim Valença (Association of Support to Oral Health Research (APESB), 2021)
Objective: To characterize the access to primary dental care and the work process of Oral Health Teams (OHTs), nationwide and by geographic region, based on data from the 3rd phase of the PMAQ-AB (the Program for Improving Access and Quality of Primary Care). Material and Methods: This was a cross-sectional study using data from the external assessments of the PMAQ-AB regarding the variables access to dental care and the work process of OHTs. The data were analyzed descriptively. Results: A significant number of healthcare users (41.2%) reported an average waiting time of 10 days to schedule dental appointments at the primary care facility (PCF). In the Northeast region, a greater number of users (48.4%) had access to dental care, with a waiting time of 7 days, whereas a smaller number of users in the Southeast region could schedule an appointment with the dentist (33.9%) and experienced a longer waiting time (17 days). Most OHTs worked in Primary Care Teams (PCTs) (85.1%), received support from Specialized Dental Care Centers (70.9%), worked with scheduled appointments and/or spontaneous demands (98.0%), listened to the users' complaints during user embracement sessions (99.0%), and scheduled the first appointment at the dental office (51.9%). Conclusion: In Brazil, 41.2% of the healthcare users had access to dental care and experienced a waiting time ranging from 7 to 17 days, depending on the geographic region. While the OHTs developed primary oral care actions, further initiatives to ensure the expansion of access to dental care are needed.